Bending properties and failure mechanisms of three-dimensional hybrid woven spacer composites with glass and carbon fibers. Issue 21 (November 2019) - Wang, Liyong; Liu, Xiaohua; Saleemi, Sidra; Zhang, Yinjiang; Qiu, Yiping; Xu, Fujun
Three-dimensional (3D) woven spacer composites are competitive materials in aerospace fields due to their excellent integrated, light-weight structure. The face sheets of the 3D woven spacer composites are crucial for the mechanical properties. In this study, 3D hybrid composites, which are composed of glass and carbon fibers in the face sheets and glass fiber in the core layer as reinforcement and epoxy resin as the matrix, were designed and fabricated. The bending test results show that with the increase of the carbon fibers in the face sheets, the normalized bending strength of hybrid spacer composites showed limited improvement, while their normalized bending moduli and bending stiffnesses were significantly improved. The optical and scanning electron microscope images of the fractured surfaces reveal that the fibers in the top face sheet, which is under compression by the indenter, are damaged first and cause the failure of the entire structure, whereas the fibers in the bottom face sheets are stretched during the bending test and slightly damaged. In addition, in the failure cross-sections, pull-out of the carbon fibers is observed due to its limited interfacial bonding with the epoxy resin. This work could help optimize 3D hybrid woven spacer composite structures for better performance and lower cost.